Development Of Arabic Language Learning Outcome Assessment Instrument Based On Hot Potatoes Application At Junior High School - Taskia Qalbi; Yusring Sanusi Baso; Yusuf T (Jurnal Pendidikan Dasar dan Keguruan, 2026)
Arabic language education at SMPIT Darul Fikri Makassar faces challenges with conventional assessments that lack interactivity, subjectivity, and fail to motivate Generation Z students, particularly in skills like qira'ah (reading), kitabah (writing), istima' (listening), and kalam (speaking). This study aims to develop a learning outcome assessment instrument based on the Hot Potatoes application using the simplified Borg and Gall Research and Development (R&D) model across eight stages: needs analysis, planning, prototype development, expert validation, revision, field testing, and final product. Primary data sources include Arabic teachers and 8th-grade students, with secondary sources like syllabi and lesson plans (RPP); data collection involved observation, interviews, questionnaires, and tests. Results indicate the instrument has very high content validity (96.43%) from Arabic, educational evaluation, and media experts, plus empirical validity with 26 out of 30 items valid. Reliability reaches 0.87 (Cronbach’s Alpha, high category), balanced difficulty levels (63% moderate), and good item discrimination. Practicality is rated very high by teachers (95.83%) and students (87.62%), thanks to automatic scoring, instant feedback, and appealing design. Effectiveness testing shows pre-test (60.20) to post-test (80.20) improvement, raising mastery from 40.60% to 85.67%, with t-value 8.724 (p=0.000) and effective gain score. The instrument proves valid, reliable, practical, and effective in enhancing learning outcomes. Overall, this development offers an innovative digital assessment model for Arabic education in Islamic schools, supporting hybrid learning post-pandemic and student motivation.